Lessons from South Africa's BITs review - Xavier Carim (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
Following an extensive review, South Africa has decided to modernise its investment protection regime in a manner that balances strong protection for investors with Constitutional requirements to safeguard the public interest, and promote sustainable development and inclusive growth. This has involved developing a new investment bill that will strengthen and clarify protection provided to all investors in South Africa as well as terminating bilateral investment treaties that pose unacceptable risks to democratic policy making in South Africa, without delivering any discernible economic benefit.
Keywords: 330